Time-Course Responses of Muscle-Specific MicroRNAs Following Acute Uphill or Downhill Exercise in Sprague-Dawley Rats - Yin, Xin; Zhao, Yan; Zheng, Yi Li; Wang, Jin Zhi; Li, Wei; Lu, Qiu Ju; Huang, Qiang Nian; Zhang, Chen Yu; Chen, Xi; Ma, Ji Zheng (Frontiers in Physiology, 2019)
Abstract: Objective: The physiological characteristics and acute responses underpinning uphill running differ from those of downhill running and remain less understood. This study aimed to evaluate time-course changes of muscle-specific microRNA (miRNA) responses in striated muscle or circulation in response to uphill and downhill running. Methods: Male Sprague-Dawley rats (n=84) were randomly assigned to a sedentary group (n=12) and an exercise group (n=72). The exercise group performed 90 min of uphill or downhill running. The striated muscle (quadriceps, gastrocnemius, soleus and cardiac muscle) or circulation (plasma, exosomes, exosome-free) levels of 6 muscle-specific miRNAs (miR-1, miR-133a, miR-133b, miR-206, miR-208a and miR-499) were assessed at rest, immediately following exercise, and during recovery (1h and 48h). Results: Our result show that miR-1 and miR-133a levels are both decreased in quadriceps following downhill running (p < 0.05) while there is no change after uphill running (p > 0.05); In gastrocnemius, both uphill and downhill running decreased miR-1 level immediately after exercise and returned to baseline during recovery (p < 0.05), interestingly, only miR-499 significantly increased following uphill running (p > 0.05); Of the cell-free miRNAs in circulation, only the miR-133b levels in plasma were not affected following uphill running (p > 0.05); the other miRNA levels significantly increased immediately after exercise (p < 0.05), decreased at 1 h and significantly increased at 48 h after exercise (p < 0.05). All selected miRNA levels in exosomes were not affected following uphill running (p > 0.05), while all selected miRNA levels significantly increased during early recovery after downhill running (p > 0.05). In addition, only the miR-133a level in the exosome-free condition showed significant changes following uphill running (p < 0.05), while miR-1, miR-133a miR-499 levels showed significant changes after downhill running (p < 0.05). Conclusion: The results indicate that miRNA undergoes dynamic changes in tissue may play an important role in regulating different stress/adaptation following uphill and downhill running. It is likely that changed miRNA levels in plasma may act as a new biomarker for monitoring whole muscular stress during recovery.